Gender, Intersections, and Institutions : Intersectional Groups Building Alliances and Gaining Voice in Germany - Davidson-Schmich, Louise K., 1968- (Book collections on Project MUSE., 2017)
Germany serves as a case study of when and how members of intersectional groups-individuals belonging to two or more disadvantaged social categories-capture the attention of policymakers, and what happens when they do. This edited volume identifies three venues through which intersectional groups are able to form alliances and generate policy discussions of their concerns. Original empirical case studies focus on a wide range of timely subjects, including the intersexed, gender and disability rights, lesbian parenting, women working in STEM fields, workers' rights in feminized sectors, women in combat, and Muslim women and girls.